Accounting for dummies - Tracy, John A.; Tracy, Tage C. (--For dummies., 2022)
Demystify your financial statements and figure out what your accountant is talking about with this straightforward roadmap to the world of accounting Few skills are as useful as a basic understanding of accounting language. And with the right resources, learning the language of business can be intuitive, empowering, and fun. Accounting For Dummies is the perfect place to start, whether you're operating a small business, just need help managing the family budget, or you're a rising star in corporate America. It's a financial blueprint for the everyday person, easy-to-understand, and full of practical advice. You'll learn the basic ABC's of accounting, how to read and understand financial statements, create best in class budgets & forecasts, craft profitable business plans, take control of your own finances, gain insight on how companies get money from investors and banks, and avoid common money mistakes that trip up even the best of us. You'll also find out how to: Diagnose the financial health of your business and make a realistic plan to grow your company Improve your own or your family's money situation with sound financial planning and understanding Understand each of the three basic financial statements and what they say about a company's past, present, and future Enhance your knowledge of how accounting functions and operates in today's digital age and cloud-based world As a useful tool for business or as a guide to your personal finances, nothing compares to accounting mastery. And once you've nailed the basics, you'll wonder how you ever lived without this universal and beautiful language.